2021
DOI: 10.3389/fcell.2021.724970
|View full text |Cite
|
Sign up to set email alerts
|

HIV Tat-Mediated Induction of Monocyte Transmigration Across the Blood–Brain Barrier: Role of Chemokine Receptor CXCR3

Abstract: HIV trans-activator of transcription (Tat), one of the cytotoxic proteins secreted from HIV-infected cells, is also known to facilitate chemokine-mediated transmigration of monocytes into the brain leading, in turn, to neuroinflammation and thereby contributing to the development of HIV-associated neurocognitive disorders (HAND). The mechanism(s) underlying HIV Tat-mediated enhancement of monocyte transmigration, however, remain largely unknown. CXC chemokine receptor 3 (CXCR3) that is expressed by the periphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…CD204 is a reliable marker of microglia-like cells from the CSF. Microglia and CNS monocytes have been suggested to play a prominent role in HIV neuropathogenesis (11,(25)(26)(27). However, myeloid cells in the CSF are challenging to analyze since their scarcity makes it difficult to characterize cell subsets through traditional flow cytometry-based methods.…”
Section: Resultsmentioning
confidence: 99%
“…CD204 is a reliable marker of microglia-like cells from the CSF. Microglia and CNS monocytes have been suggested to play a prominent role in HIV neuropathogenesis (11,(25)(26)(27). However, myeloid cells in the CSF are challenging to analyze since their scarcity makes it difficult to characterize cell subsets through traditional flow cytometry-based methods.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in HIV-positive patients, CXCR3-positive astrocytes are found around cerebral infarction, and the number of these cells decreases with the distance from the infarcted tissue [42]. A similar phenomenon can be seen in patients with ischemic stroke, in which the accumulation of CXCR3-positive astrocytes can be seen around the infarction.…”
Section: Nervous System Diseasementioning
confidence: 65%
“…In diseased diseases, microglia-mediated neuronal and glial cell damage is mainly caused by proinflammatory cytokines, which ultimately leads to immune cells participating in the transendothelial migration of blood-brain barrier and subsequent neuronal damage [41]. For example, in HIV-positive patients, CXCR3-positive astrocytes are found around cerebral infarction, and the number of these cells decreases with the distance from the infarcted tissue [42]. A similar phenomenon can be seen in patients with ischemic stroke, in which the accumulation of CXCR3-positive astrocytes can be seen around the infarction.…”
Section: Aberrant Expression Of Cxcr3 In Multiple Diseasesmentioning
confidence: 99%
“…Within the myeloid lineage, an increase in CSF1R expression is associated with myeloid cell differentiation and chemotaxis towards tissue-derived ligands 57 , 59 . Contrarily, CXCR3 is highly expressed in peripheral monocytes and is involved in monocyte transmigration into the CNS, where enhanced receptor-ligand binding leads to internalization of the receptor 60 64 . In line with these findings, we observed that OPC and SP media resulted in changes in gene expression consistent with a CNS-mimicking microenvironment in contrast to MM.…”
Section: Discussionmentioning
confidence: 99%